Complete mitochondrial genome of Hepialus gonggaensis (Lepidoptera: Hepialidae), the host insect of Ophiocordyceps sinensis. (1st November 2016) - Shi, Ping; Lu, Zenghui; He, Yuanchuan; Chen, Shijiang; Qin, Shaorong; Qing, Yuling; Yan, Jun
Abstract: The complete mitochondrial genome sequence of Hepialus gonggaensis was sequenced for the first time. The complete mtDNA sequence was 15, 940 bp in length and contained 13 protein-coding genes, two rRNA genes, 22 tRNA genes, and an AT-rich region, the gene composition and the arrangement of which were identical to other insects of Hepialidae. The overall base composition of the heavy strand was 41.14% A, 40.24% T, 11.17% C, and 7.45% G, with an AT content of 81.37%. The necleotide sequence data of 13 protein-coding genes of H. gonggaensis and other 10 Lepidoptera species were used for constructing the phylogenetic tree. It revealed that H. gonggaensis and other four Hepialidae species were clustered to a clade with high bootstraps values.